Impact of epidermal growth factor single‐nucleotide polymorphism on recurrence of hepatocellular carcinoma after hepatectomy in patients with chronic hepatitis C virus infection. Issue 6 (15th May 2014) - Yoshiya, Shohei; Fujimoto, Yukiko; Bekki, Yuki; Konishi, Hideyuki; Yamashita, Yo‐ichi; Ikegami, Toru; Yoshizumi, Tomoharu; Shirabe, Ken; Oda, Yoshinao; Maehara, Yoshihiko
<x xml:space="preserve">Abstract</x> Epidermal growth factor (EGF) gene single‐nucleotide polymorphism (SNP) is associated with an increased risk of hepatic tumors. The study aimed to elucidate the impact of EGF SNP and EGF receptor (EGFR) expression on the recurrence of hepatocellular carcinoma (HCC) after hepatectomy. To examine the impact of EGF SNP and EGFR on recurrent HCC, we retrospectively analyzed 141 HCC patients with chronic hepatitis C virus infection who underwent curative hepatectomy. The EGF *61 GG allele was present in 69 patients (48.9%), AG in 56 (39.7%) and AA in 16 (11.4%). The AA group had a significantly lower rate of intrahepatic metastasis (0% vs 16.5%, P = 0.02), lower serum EGF concentration (26.3 ± 15.9 pg/mL vs 43.4 ± 30.5 pg/mL, P = 0.02) and lower proportion of early recurrence (≤2 years; 28.6% vs 71.2%, P = 0.03) than the AG/GG group. The AA group had significantly higher recurrence‐free survival than the AG/GG group (P = 0.04), but there was no significant difference in overall survival between these two groups (P = 0.97). High versus low EGFR expression analyzed by immunohistochemical staining in cancer cells was not significantly associated with overall survival (P = 0.37) or recurrence‐free survival (P = 0.39). Therefore, EGF *61 AA was associated with a lower risk of recurrence after curative hepatectomy for HCC in patients with hepatitis C virus infection than other genotypes, but EGFR expression in cancer cells was not significantly associated with prognosis.